A dysbiotic gut microbiome suppresses antibody mediated-protection against Vibrio cholerae - John C. Macbeth (Elsevier, 2021)
Summary: Cholera is a severe diarrheal disease that places a significant burden on global health. Cholera’s high morbidity demands effective prophylactic strategies, but oral cholera vaccines exhibit variable efficacy in human populations. One contributor of variance in human populations is the gut microbiome, which in cholera-endemic areas is modulated by malnutrition, cholera, and non-cholera diarrhea. We conducted fecal transplants from healthy human donors and model communities of either human gut microbes that resemble healthy individuals or those of individuals recovering from diarrhea in various mouse models. We show microbiome-specific effects on host antibody responses against Vibrio cholerae, and that dysbiotic human gut microbiomes representative of cholera-endemic areas suppress the immune response against V. cholerae via CD4+ lymphocytes. Our findings suggest that gut microbiome composition at time of infection or vaccination may be pivotal for providing robust mucosal immunity, and suggest a target for improved prophylactic and therapeutic strategies for cholera.